Congenital hepatic fibrosis in Holando Argentino calf: first report in Argentina - Indart, Mirentxu; Yaniz, María G. de; García, Jorge P.; Bence, Ángel R.; Negrette, Marcial S. (Brazilian Journal of Veterinary Pathology, 2019)
A case of congenital hepatic fibrosis in a 10-month-old calf is described. The calf had been raised in a feed lot for the past 173 days and exhibited loss of body condition and depression, followed by death. The most remarkable macroscopic lesions observed during necropsy were: jaundice, hepatomegaly with a multilobulated liver surface and diffuse pale brown colour of the parenchyma. Microscopically, the portal tracts were thickened and connected to each other by abundant fibrous tissue, delimiting irregular lobules of hepatocytes and occasional fibrosis of the central veins (perisinusoidal scars) and hyperplasia of embryonal bile ducts. Immunohistochemistry staining of the cytoplasm of the bile ducts was positive to AE1/AE3 and cell proliferation nuclear antigen (PCNA). The findings at necropsy, together with the results of the histopathological and immunohistochemistry studies, confirmed the diagnosis of congenital hepatic fibrosis.